2017
DOI: 10.1016/j.rmed.2017.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of long-term imatinib therapy for patients with pulmonary veno-occlusive disease and pulmonary capillary hemangiomatosis

Abstract: Imatinib improved exercise capacity, hemodynamics and survival in patients with PVOD/PCH. In patients with PVOD/PCH, who have no effective medical therapy available, imatinib might function as a bridge to lung transplantation, and may become a potential therapeutic option to improve their survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…The authors did not observe the development of subdural haematomas, but two patients in the imatinib-treated group died of infective complications. Nevertheless, median survival in the group treated with imatinib was over 4 years, which is unusual for PVOD/PCH patients [49].…”
Section: Therapy and Prognosismentioning
confidence: 93%
See 2 more Smart Citations
“…The authors did not observe the development of subdural haematomas, but two patients in the imatinib-treated group died of infective complications. Nevertheless, median survival in the group treated with imatinib was over 4 years, which is unusual for PVOD/PCH patients [49].…”
Section: Therapy and Prognosismentioning
confidence: 93%
“…Imatinib resulted in the significant improvement of the World Health Organisation (WHO) functional class and serum BNP concentration, as well as in the decrease of mean pulmonary artery pressure and prolonged survival [49]. The authors did not observe the development of subdural haematomas, but two patients in the imatinib-treated group died of infective complications.…”
Section: Therapy and Prognosismentioning
confidence: 97%
See 1 more Smart Citation
“…Pulmonary veno-occlusive disease and/or pulmonary capillary hemangiomatosis (PVOD/PCH) are categorized as group 1 pulmonary hypertension, with no effective medical therapy except for lung transplantation. Recently, a small observational study [96] found that imatinib improved survival time and enhanced exercise capacity in patients with PVOD/PCH and may function as a bridge therapy to lung transplantation.…”
Section: Metabolism Dysfunctionmentioning
confidence: 99%
“…However, imatinib failed to be a treatment option in the phase III trial because of the adverse events despite its efficacy (Hoeper et al 2013). Recently it has been reported that imatinib could improve functional capacity in PVOD patients who were clinically diagnosed, although in some cases the diagnosis is made only pathologically after autopsy or lung transplantation (Overbeek et al 2008;Ogawa et al 2017).…”
Section: Introductionmentioning
confidence: 99%